Proteoglycan-Dependent Endo-Lysosomal Fusion Affects Intracellular Survival of Salmonella Typhimurium in Epithelial Cells - Galeev, Alibek; Suwandi, Abdulhadi; Bakker, Hans; Oktiviyari, Ade; Routier, Françoise H.; Krone, Lena; Hensel, Michael; Grassl, Guntram A. (Frontiers in Immunology, 2020)
Proteoglycans (PGs) are glycoconjugates which are predominately expressed on cell surfaces and consist of glycosaminoglycans (GAGs) linked to a core protein. An initial step of GAGs assembly is governed by the β-D-xylosyltransferase enzymes encoded in mammals by the XylT1/XylT2 genes. PGs are essential for the interaction of a cell with other cells as well as with the extracellular matrix. A number of studies highlighted a role of PGs in bacterial adhesion, invasion, and immune response. In this work, we investigated a role of PGs in Salmonella enterica serovar Typhimurium (S. Typhimurium) infection of epithelial cells. Gentamicin protection and chloroquine resistance assays were applied to assess invasion and replication of S. Typhimurium in wild-type and xylosyltransferase-deficient (ΔXylT2) Chinese hamster ovary (CHO) cells lacking PGs. We found that S. Typhimurium adheres to and invades CHO WT and CHO ΔXylT2 cells at comparable levels. However, 24 hours after infection, proteoglycan-deficient CHO ΔXylT2 cells are significantly less colonized by S. Typhimurium compared to CHO WT cells. This proteoglycan-dependent phenotype could be rescued by addition of PGs to the cell culture medium, as well as by complementation of the XylT2 gene. Chloroquine resistance assay and immunostaining revealed that in the absence of PGs, significantly less bacteria are associated with Salmonella-containing vacuoles (SCVs) due to a re-distribution of endocytosed gentamicin. Inhibition of endo-lysosomal fusion by a specific inhibitor of phosphatidylinositol phosphate kinase PIKfyve significantly increased S. Typhimurium burden in CHO ΔXylT2 cells demonstrating an important role of PGs for PIKfyve dependent vesicle fusion which is modulated by Salmonella to establish infection. Overall, our results demonstrate that PGs influence survival of intracellular Salmonella in epithelial cells via modulation of PIKfyve-dependent endo-lysosomal fusion.